2011
DOI: 10.1074/jbc.m111.232009
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived Neurotrophic Factor (BDNF) Enhances GABA Transport by Modulating the Trafficking of GABA Transporter-1 (GAT-1) from the Plasma Membrane of Rat Cortical Astrocytes

Abstract: Background: Transport of GABA into astrocytes is crucial for excitability control. Results: The neurotrophin BDNF, through TrkB-t receptor activation, enhances GABA transport into astrocytes, which requires adenosine A 2A receptor signaling. Conclusion: BDNF plays an active role in the synaptic clearance of GABA. Significance: This new regulatory role for TrkB-t receptors discloses their relevance for excitability control at the tripartite synapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 60 publications
7
65
0
Order By: Relevance
“…It is technically difficult to know to what extent adenosine receptor internalization affects GABA transport in astrocytes. In fact, GABA transport into astrocytes is itself affected by inhibitors of arrestin-dependent endocytosis [20] that would be required to prevent adenosine receptor internalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is technically difficult to know to what extent adenosine receptor internalization affects GABA transport in astrocytes. In fact, GABA transport into astrocytes is itself affected by inhibitors of arrestin-dependent endocytosis [20] that would be required to prevent adenosine receptor internalization.…”
Section: Discussionmentioning
confidence: 99%
“…As it is the case for GABA transporters in astrocytes [20], membrane proteins usually recycle, being internalized and sent back to the membrane in a controlled way. Biotinylation assays showed that exposure to either A 1 R or A 2A R agonists led to decreases in surface expression of A 1 R, and to similar increases in the A 1 R levels in intracellular fractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While A 1 receptors are widely expressed throughout the brain, A 2A receptors are most abundant in the basal ganglia, but these receptors are also present at lower density in other brain regions, namely the hippocampus. The molecular mechanisms by which the A 2A receptor controls neuronal excitability and synaptic plasticity have been extensively studied [10][11][12][13][14]. Activation of the A 2A receptor stimulates glutamate release and prevents its uptake, thus resulting in increased synaptic levels of this excitatory amino acid [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As we now show, A 2A R also contributes to BDNF-mediated inhibition of GABA release; this action of BDNF being known to result from GABA transporters modulation [16]. Considering the astrocytic component of neuronal communication, A 2A Rs also contribute BDNF-mediated modulation of GABA transport [25]. The different actions of A 2A Rs in different synapses and their ability to affect different actions of BDNF at specific sites of the tripartite synapse may allow to finely shape excitatory and inhibitory signals, thus to fine tune neuronal function.…”
Section: Discussionmentioning
confidence: 58%